Personalized approaches to the treatment of hemophilia A and B. (August 2015) - Simhadri, Vijaya L; Banerjee, Aditi Sengupta; Simon, Jonathan; Kimchi-Sarfaty, Chava; Sauna, Zuben E
The recognition that individuals respond differently to the same medication is not new and dates almost to the founding of western medicine. In the last century it came to be recognized that genetic factors influence the heterogeneity of individual responses to medications with respect to both toxicity and effectiveness. Nonetheless, it has been challenging to integrate pharmacogenetic approaches in the routine practice of medicine as the identification of biomarkers is difficult due to the inherent complexity of biological systems. Here, we present potential applications of pharmacogenetics in managing hemophilia A and B. We discuss how predicting and circumventing immunogenicity, an important impediment to treating hemophilia patients, particularly lends itself to a pharmacogenetic approach. In addition, we discuss new trends toward personalizing the management of hemophilia in clinical settings.